Mating type control in Saccharomyces cerevisiae: a frameshift mutation at the common DNA sequence, X, of the HML alpha locus. - Tanaka, K (1984)
A mutation defective in the homothallic switching of mating type alleles, designated hml alpha-2, has previously been characterized. The mutation occurred in a cell having the HO MATa HML alpha HMRa genotype, and the mutant culture consisted of ca. 10% a mating type cells, 90% nonmater cells of haploid cell size, and 0.1% sporogenous diploid cells. Genetic analyses revealed that nonmater haploid cells have a defect in the alpha 2 cistron at the MAT locus. This defect was probably caused by transposition of a cassette originating from the hml alpha-2 allele by the process of the homothallic mating type switch. That the MAT locus of the nonmater cells is occupied by a DNA fragment indistinguishable from the Y alpha sequence in electrophoretic mobility was demonstrated by Southern hybridization of the EcoRI-HindIII fragment encoding the MAT locus with a cloned HML alpha gene as the probe. The hml alpha-2 mutation was revealed to be a one-base-pair deletion at the ninth base pair in the X region from the X and Y boundary of the HML locus. This mutation gave rise to a shift in the open reading frame of the alpha 2 cistron. A molecular mechanism for the mating type switch associated with the occurrence of sporogenous diploid cells in the mutant culture is discussed.